The role of strategic planning in promoting rural ecotourism (Case study : Zagros region) - Soltani Moghaddas, Reihaneh (2008)
Nowadays, ecotourism is a new approach in the world. ecotourism as a purposive trip to natural settings and habitats and with the aims of cultural preservation and conservation is a viable economic alternative. Ecotourism possesses some positive environmental , economic ,and social impacts among which conduction of environmental protection measures, income generation , creation of job opportunities, and promotion of host communities cultural values need considerable attention .There are many attractions in these regions. Because of varieties of natural landscapes, potentials of these regions are very different.